Pengaruh Islamic Branding dan Islamic Service Quality terhadap Loyalitas Nasabah PT Bank Muamalat Indonesia, Tbk KC Medan Balai Kota dengan Customers Satisfaction sebagai Variabel Intervening - Ramdanil Fajar; Sri Ramadhani; Muhammad Lathief Ilhamy Nasution (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to determine the effect of Islamic branding and Islamic service quality on customer loyalty at PT Bank Muamalat Indonesia, Tbk, Medan Balai Kota Branch, with customer satisfaction as an intervening variable. This is a quantitative study. Data collection used a questionnaire with a sample size of 100 respondents using a random sampling technique. The obtained data were then processed using SPSS 25. Instrument tests used included validity and reliability tests. The classical assumption tests used included normality, multicollinearity, and heteroscedasticity. Hypothesis testing used t-tests, f-tests, and coefficient of determination tests. Data analysis used path analysis. The results of the first t-test indicate that Islamic branding, Islamic service quality, and customer satisfaction have a positive and significant effect on customer loyalty. The results of the second t-test indicate that Islamic branding and Islamic service quality have a positive and significant effect on customer satisfaction. Customer satisfaction can mediate the relationship between Islamic branding and service quality.